E-Government And the Digitalization of Governmental services (Citizen-Centric Services) - Kamel, Mahmoud Ahmed Mahmoud Ahmed (2024)
There are several factors that hinder the general public for not availing the e-government services because of less or no awareness and satisfaction among the citizens about the available e-government services. The purpose of this research is to analyse the impact of e-government services on the satisfaction of citizens. This research adopted a survey research strategy and collected the required by using a questionnaire with closed-ended questions. The questionnaire was designed on Google Forms so that the data could easily be collected from the participants. The data analysis was conducted in Microsoft Excel and SPSS software. In Microsoft Excel, the frequency distribution of participants' responses was collected. Then the data was put in SPSS to calculate the reliability and normality so that parametric data analysis could be conducted on the data for the achievement of research objectives. Furthermore, the comparison of means across various demographic groups was carried out by using the analysis of variance (ANOVA) test and the association between the variables was indicated by using Pearson correlation analysis. The findings obtained from this thesis indicated that the satisfaction of citizens is concerned it significantly varied across the gender, age, and qualification of the German citizens. Furthermore, according to the results obtained from the Pearson correlation analysis, the various variables of perceived usefulness, perceived ease of use, transparency, privacy and security, and trust of citizens were found to be in positive association with the variables of the satisfaction of the German citizens.